Innovative Instruction of Law Teaching and Learning: Using Visual Art, Creative Methods, and Technology to Improve Learning - Khatib, Abdullah al; Shaban, Mohamad Sadeg (International Journal of Membrane Science and Technology, 2023)
This study mainly focuses on the need for innovative instruction of law teaching and learning practices at the present time and how the law subject communicates to the students innovatively and learning from various innovative instruction with the help of advanced technologies. This study will examine several innovative instructions used at the college of law at United Arab Emirates University (UAEU) and their effect on students’ achievements. The methodology used in this study was collected from the course evaluation by students in various classes. This was exhibited the students’ opinions in a form of a survey that follows Likert scale. This survey was developed by the UAEU Office of Institutional Effectiveness. In addition to the five open-ended questions which are a part of the survey too. The data analyzed using the means and the percentage of the responses to the questions. In addition, the use of quotations of the student’s narrative response to the open-ended question. The participants for this study were 85 students studying/various courses at the college of law at UAEU University. The study included both genders. The results of the innovative instructions transferred the teaching and learning at the college of law at UAEU from the traditional curriculum to innovative instructions based on simulation, application, critical thinking, and logical reasoning. This transformation represented an important point in the change of law education from the classical school of law education to the applied school that relies on the idea of ??application as principles for evaluating legal theory.